1989
DOI: 10.1038/bjc.1989.280
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase isoenzymes in human tumours and tumour derived cell lines

Abstract: Edinburgh, Edinburgh Royal Infirmary, Edinburgh EH3 9 YW; and 3Department of Clinical Oncology, Newcastle General Hospital, Newcastle-upon-Tyne, UK.Summary An increasing body of evidence indicates that glutathione S-transferases play a role in the intrinsic and acquired resistance of tumours to anticancer drugs. In view of the wide use of tumour cell lines to understand the factors which confer either sensitivity or resistance to chemotherapeutic agents we have determined glutathione S-transferase (GST) activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 19 publications
4
22
0
3
Order By: Relevance
“…A number of studies have reported the distribution of GSTP1 exon 5 polymorphisms in different populations (4,(10)(11)(12). The results of the present study indicated that the mutant G allele of the GSTP1 gene occurred at a frequency of 23.0% in a Chinese population, and that the A/A, A/G, and G/G genotypes of the GSTP1 gene occurred at frequencies of 56.6, 40.8 and 2.6%, respectively.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…A number of studies have reported the distribution of GSTP1 exon 5 polymorphisms in different populations (4,(10)(11)(12). The results of the present study indicated that the mutant G allele of the GSTP1 gene occurred at a frequency of 23.0% in a Chinese population, and that the A/A, A/G, and G/G genotypes of the GSTP1 gene occurred at frequencies of 56.6, 40.8 and 2.6%, respectively.…”
Section: Discussionsupporting
confidence: 51%
“…The frequencies of the GSTP1 exon 5 polymorphism genotypes and the mutant T allele in populations from different regions reported by relevant studies are listed in Table VII. As shown in Table VII, the mutant G allele is most frequently observed in African Americans (42%), and occurs least frequently in Chinese (23%); while the frequency has been found to be 33-36% in European Americans, British and other Caucasians, and 26% in a Japanese population (4,(10)(11)(12). Although these samples may not be truly representative of their respective race, these results at least suggest the difference in the distribution of GSTP1 alleles and genotypes among Chinese, African Americans and Europeans.…”
Section: Discussionmentioning
confidence: 99%
“…Several resistant cell lines have been shown to overexpress GST [81]. GSTs are detoxification enzymes conjugated of glutathione to the electrophilic center of various drugs and resulting in excretion of polar molecules.…”
Section: Glutathione-s-transferease (Gst)mentioning
confidence: 99%
“…Kelley et al [20] reported that the average level of GSTs was substantially elevated in the cancer tissues than the levels in normal breast tissue from the same patient. An increasing body of evidence indicates that GSTs play a role in the intrinsic and acquired resistance of tumors to anticancer drugs [21]. Consequently, the increased activity of the GSTs in the breast tumor may be associated with the developed resistance of the tumors against the anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%